Fortifikasi Nak Nan Jelly Bog Segamur - hasbi, habid al; sutanta (Universitas Sahid Surakarta, 2024)
Abstract: Abundant banana stem waste is often wasted and becomes an environmental problem. In fact, research results show that banana stems are rich in benefits, one of which is the potential as an anti-obesity agent. Seeing this potential, the community service team tried to process banana stem waste into nutritious and economically valuable food products. This community service activity focused on assisting PKK Metuk mothers in processing banana stems into innovative food products. With intensive training and assistance, it is hoped that PKK mothers can produce value-added food products from banana stem waste. In addition to providing health benefits to the community, this activity is also expected to improve the community's economy through the development of small and medium enterprises based on local resources. The results of this community service activity show that the processing of banana stem waste into food products can be successful. PKK mothers succeeded in producing food products that are not only beneficial for health, but also have good market potential. This success proves that banana stem waste can be a valuable resource if managed properly. Keywords: Musa paradisiaca, economy, health